Comorbidities in patients with epilepsy: Frequency, mechanisms and effects on long‐term outcome. (26th July 2021) - Giussani, Giorgia; Bianchi, Elisa; Beretta, Simone; Carone, Davide; DiFrancesco, Jacopo C.; Stabile, Andrea; Zanchi, Clara; Pirovano, Marta; Trentini, Claudia; Padovano, Giada; Colombo, Matteo; Cereda, Diletta; et al.
Abstract: Objective: To assess frequency, types, and mechanisms of comorbidities in people with epilepsy and verify their association with disease features and outcome. Methods: This cohort study was performed in 13 Italian epilepsy centers with nationwide distribution and accurate records. Eligible patients were children and adults diagnosed before December 31, 2005, and followed for a minimum of 10 years. Two pairs of raters independently reviewed patients' records and classified each comorbidity. In case of disagreement, a third reviewer made the final decision. Comorbidities were classified according to type (organ/system) and underlying mechanism (causal, shared risk factors, chance association). Comorbidity types and mechanisms were described in the entire sample and according to epilepsy prognostic patterns (sustained remission, relapsing‐remitting course, no remission). Results: Of 1006 included patients, 266 (26.4%) had at least one comorbidity. The most common were developmental/perinatal (7.5% of cases), psychiatric (6.2%), cardiovascular (5.3%), and endocrine/metabolic (3.8%). Among 408 reported comorbidities, the underlying mechanisms were, in decreasing order, chance association (42.2%), shared risk factors (31.1%), and causal (26.7%). Psychiatric diseases were present in 13.3% of patients with no remission, 5.9% of patients with relapsing‐remitting course, and 4.8% of patients with sustained remission ( p = .016). The corresponding numbers for endocrine/metabolic diseases were respectively, 9.6%, 3.4%, and 2.9% ( p = .013); for respiratory diseases were 3.6%, .3%, and .3% ( p = .001), and for urogenital diseases were 3.6%, .7%, and 1.6% ( p = .048). The association of endocrine/metabolic, psychiatric, and respiratory comorbidities with epilepsy prognosis was confirmed by multivariable analysis adjusted for the main demographic and clinical variables, with patients with these comorbidities showing a lower probability of achieving remission. Significance: Comorbidities in epilepsy are not uncommon and reflect differing underlying mechanisms. Psychiatric, endocrine/metabolic, and respiratory disorders are associated with a worse long‐term epileptological outcome.